The Effect of Zakat Distribution and the Growth of the Halal Industry on the Human Development Index and Its Impact on Indonesia's Unemployment Rate - Dul Candra; Baitul Hamdi; Sri Herianingrum; Hafidhotul Amaliyah (Jurnal Ilmiah Ekonomi Islam, 2023)
This paper aims to analyze further the effect of zakat distribution and the growth of the halal industry on the HDI and unemployment rates in Indonesia, as well as to measure and analyze the direct and indirect effects of zakat distribution and the growth of the halal industry on the unemployment rate through the human development index in Indonesia. This research is quantitative research using a path analysis approach. The data sources used are secondary data sources in the form of 2014-2020 time series data published by BAZNAS, Salamgateway, and the Indonesian Central Statistics Agency (BPS). The results of this study show that the distribution of zakat and the growth of the halal industry have no significant effect on Indonesia's HDI. The distribution of zakat and HDI has a significant negative effect on the unemployment rate in Indonesia, while the halal industry positively influences the unemployment rate. The distribution of zakat and the halal industry's growth indirectly have no effect on the unemployment rate through the Human Development Index. The research is expected to contribute to the Indonesian government to use of zakat and the halal industry as an instrument to reduce Unemployment in Indonesia, namely by increasing regulations related to the effectiveness of zakat distribution and the halal industry so that the impact will be even more significant.